Neuropeptide Y receptor 1 is expressed by B and T lymphocytes and mast cells in infantile haemangiomas. (10th January 2017) - Tan, Elysia M. S.; Blackwell, Max G.; Dunne, Jonathan C.; Marsh, Reginald; Tan, Swee T.; Itinteang, Tinte
Abstract: Aim: We investigated the expression of neuropeptide Y (NPY), NPY receptor 1 (NPYR1) and NPY receptor 2 (NPYR2) in infantile haemangiomas (IHs). Methods: Immunohistochemical (IHC) staining was performed on proliferating IHs from six patients aged 4–13 (mean 8.7) months and involuted IHs from six patients aged 5–59 (mean 18.7) years, for the expression of NPY, NPYR1 and NPYR2. Protein and messenger ribonucleic acid expression corresponding to these proteins was investigated by Western blotting and NanoString analysis, respectively. Results: IHC staining, Western blotting and NanoString analysis demonstrated the presence of NPYR1, but not NPYR2, within proliferating and involuted IHs. IHC staining showed NPYR1 was expressed by B and T lymphocytes expressing CD45 and mast cells expressing tryptase. IHC staining demonstrated the presence of NPY on the NPYR1 + cells, but it was not detected by Western blotting or NanoString analysis. Conclusion: NPYR1, but not NPYR2, was present in IHs. The localisation of NPYR1 to B and T lymphocytes and mast cells suggests its role in the biology of IHs. The demonstration of NPY on the NPYR1 + cells, without active transcription, suggests that NPY was not being produced within IHs.